ECOLOGICAL ANALYSIS OF GELAM (Melaleuca cajuputi) ON PEATLAND IN SOUTH KALIMANTAN - Yudi Firmanul Arifin; Siti Hamidah; Yulian Firmana Arifin (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Until now the raw material of wood especially Gelam (Melaleuca cajuputi) for supporting the construction of housing and other infrastructures is increasingly demand in Indonesia. On the Island of Borneo that partly consists of peat swamps needs Gelam very large and continuous, particularly for residential development. Ecological aspects are very important for supporting the silvicultural strategies. The aim of this study is to analyze ecological aspects which are very influence especially physical and chemical soil properties and microclimate as well. The utilization of study is to determine the silvicultural strategies for continuing production and conservation of Gelam in the future. The method was used a field survey around Gelam forest and did collecting samples and measuring there. The results showed in South Borneo the potency of Gelam is only 2,9-7,1 m3/ha and decreasing yearly. Normally Gelam with a diameter <4 cm have been cut down, as well as > 30 cm. Gelam can grow on the peat swamp forest where the soil was low pH 3.5-3.9. Most of pH of soil in these areas was influenced by phyrite (FeS2 of 0.4-2.2% and highest of Fe 90-302 ppm. C organic in the soil was included low-moderate 5.5-10.0%. Result of soil physic analysis showed composition of sand, dust, and clay of 9 : 54 : 57 % respectively. Temperature and humidity around peat swamp forest areas where was found Gelam were 31-33oC and 63-73% respectively. Most of areas around Gelam were grown Gelam Tikus (Syzygium inophylla) and some kind of shrubs.Key words: Gelam, potency, ecological aspects, silviculture